2017
DOI: 10.1111/ijsa.12172
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study of current performance management practices: Human resource executives’ perspectives

Abstract: A survey of performance management (PM) practices in 101 U.S. organizations explored whether their PM systems, as perceived by human resources (HR) executives, reflect the best practices advocated by researchers to provide a benchmark of current PM practices. Results suggest that many of the PM practices recommended in the research literature are employed across the organizations surveyed, but several gaps between research and practice remain. Results also indicated that the majority of PM systems are viewed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
52
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 69 publications
1
52
1
4
Order By: Relevance
“…Prior studies show that this reform may fail when, for example, appraisal is separated from consequences (Liu & Dong, ), when pay‐for‐performance is not based on objective performance standards (Randma‐Liiv, ), and when feedback lacks employee input and participation (Chiang & Birtch, ). Hence, a combined approach is increasingly used (e.g., Gorman, Meriac, Roch, Ray, & Gamble, ). Finally, in so far as many reform programs involve matters of employee performance, findings from this study may have broader relevance to other public sector reforms where, for example, employee performance or executive accountability also matter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies show that this reform may fail when, for example, appraisal is separated from consequences (Liu & Dong, ), when pay‐for‐performance is not based on objective performance standards (Randma‐Liiv, ), and when feedback lacks employee input and participation (Chiang & Birtch, ). Hence, a combined approach is increasingly used (e.g., Gorman, Meriac, Roch, Ray, & Gamble, ). Finally, in so far as many reform programs involve matters of employee performance, findings from this study may have broader relevance to other public sector reforms where, for example, employee performance or executive accountability also matter.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies show that this reform may fail when, for example, appraisal is separated from consequences (Liu & Dong, 2012), when pay-forperformance is not based on objective performance standards (Randma-Liiv, 2005), and when feedback lacks employee input and participation (Chiang & Birtch, 2010). Hence, a combined approach is increasingly used (e.g., Gorman, Meriac, Roch, Ray, & Gamble, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…These qualitative text descriptions of employee performance frequently accompany traditional numerical ratings (Brutus, ) and offer rich contextual information about employee performance, such as descriptions of competency behaviors, goal attainment, and general observations in line with situational factors. In a recent survey of senior human resources leaders, Gorman, Meriac, Roch, Ray, and Gamble () found that 84% of companies use written summaries within performance appraisals, a proportion that clearly warrants attention toward this topic.…”
mentioning
confidence: 99%
“…Training efforts seek to change knowledge, skills, attitudes, or behaviors (Bell, Tannenbaum, Ford, Noe, & Kraiger, 2017), and in the PA context that is manifested by raters properly using rating scales and mapping ratee behavior to appropriate labels on those scales. Given the success of PA training, it is encouraging to find that rater training may be applied frequently in practice, as shown by Gorman, Meriac, Roch, Ray, and Gamble (2017) in a recent survey of human resources (HR) executives. Specifically, in a sample of 101 senior HR leaders, Gorman and colleagues found that 76% of companies provide PA training to managers, and 28% do so yearly.…”
Section: Introductionmentioning
confidence: 99%
“…First, while Gorman et al (2017) use of senior leaders ensures respondents are familiar with company HR practices, it does not guarantee they are fully aware of all the details of their rater training protocols, or more importantly, which employees participated in training. Those in senior positions focus more heavily on strategic issues (Mumford, Campion, & Morgeson, 2007) and may be forced to rely upon what their subordinates tell them regarding training practices.…”
Section: Introductionmentioning
confidence: 99%